2020
DOI: 10.15625/2525-2518/58/6/15237
|View full text |Cite
|
Sign up to set email alerts
|

Indoor and outdoor relationships of particle with different sizes in an apartment in Hanoi: mass concentration and respiratory dose estimation

Abstract: This paper presents data on the size characterization concentration of PM0.1, PM0.5, PM1, PM2.5, PM10, TSP in indoor and outdoor air of a residential apartment in two seasons (winter and summer) in Hanoi, Vietnam. These particles with different sizes were taken by 5 stage impactors (Nano sampler 3182, KINOMAX). Daily average concentrations of coarse particles (PM10) and fine particles (PM2.5) indoors and outdoors exceeded the WHO recommended values. In winter, the concentrations of PM0.5, PM1, PM2.5 and PM10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The study in Hanoi reported that the average dust concentrations. including PM 2.5, PM 10, and indoor TSP exceeded the quality standard values and outdoor dust concentrations [35].…”
Section: Discussionmentioning
confidence: 86%
“…The study in Hanoi reported that the average dust concentrations. including PM 2.5, PM 10, and indoor TSP exceeded the quality standard values and outdoor dust concentrations [35].…”
Section: Discussionmentioning
confidence: 86%
“…In addition, the mass concentrations by different monitoring sites have attention as follows, urban > suburban > rural. In Vietnam, many studies of PM 0.1 in Hanoi, the capital city in Vietnam, are more progressive than in other SEA cities [28,[30][31][32][33][34][35]. The results show that mass concentrations in different environments in Hanoi ranged from 1 to 17 µg/m 3 .…”
Section: Pm 01 Mass Concentration In Southeast Asia Atmospherementioning
confidence: 97%
“…Hanoi is the capital city (with a dense population -about ten million people -only about 3000 square kilometers in area -a small city) located in the north of Vietnam. Recently, environmental issues have emerged as an urgent situation for the capital, especially air quality (Le Ha et al, 2020;Ly et al, 2018).…”
Section: Study Area and Samplingmentioning
confidence: 99%
“…According to statistics from the Ministry of Transport (Vietnam), 70% of the amount of smog-causing air pollution in Hanoi is due to the heavy tra c (https://mt.gov.vn/moitruong/Pages/ChiTietTin.aspx?groupID=1129&IDNews=52054). Although there are many studies on the particulate matter (TSP) content over time and the characteristics of heavy metals in aerosols (Le Ha et al, 2020;Ly et al, 2018;Phan et al, 2020), there are very rare studies referring to natural radionuclides speci cal the 210 Po in the atmosphere aerosols in Vietnam. According to the WHO report, in Vietnam, there were more than 60,000 deaths related the air pollution in 2016 (https://www.who.int/vietnam/news/detail/02-05-2018 -more-than-60-000-ca-vong-in-viet-nam-eachyear-Link-to-air-Pollution).…”
Section: Introductionmentioning
confidence: 99%